The effectiveness of learning Object-Oriented Programming concepts through role playing game among undegraduate students - Wong, Yoke Seng (2020)
This research aims to examine the effectiveness of learning the concept of Object Oriented Programming (OOP) through role-playing games among undergraduate students. A framework on game-based learning (GBL) has been developed and a variety of platform games (computer-based and mobile) titled Odyssey of Phoenix have been developed. The development of this game has combined the concept of constructive alignment and design of game elements with appropriate OOP learning content. A total of nine experts were involved in the validity of game design and validity of learning content with each having more than five years of experience. A pilot test was conducted involving 20 students. This study uses a quantitative approach through quasi- experimental pre-test and post-test involving a randomly selected sample of 214 first year undergraduate students in computer science from three institutions of higher learning in Malaysia. A total of 107 people were placed as treatment groups and a total of 107 people were placed as control groups. Data were analyzed using parametric inference statistics such as t-test and variance analysis to test the hypothesis. The t-test results showed that the mean score was high for the treatment group which was 7.36 (M=0.657, SD=9.295) compared to the control group (M=0.731, SD=8.833), t(107)=0.025, p=.0001). The results of the variance analysis showed that the effectiveness of student performance was significant (F=17.6241, p<0.05) for the entire OOP topic. From the score analysis, the mean for the pre-test of the control group was 17.89 while the post-test was 18.61 (difference: 0.72). The mean for the pre-treatment group test was 19.36 while the post-test was 21.99 (difference: 2.63). The results of the scores showed that the performance of the treatment group was better than that of the control group on the overall understanding of the topic. In conclusion, GBL using multi- platform games is found to be very effective as a learning material for a better understanding in learning the concept of OOP. This study implies that the continuous use of GBL can increase its effectiveness in teaching and learning the concept of OOP as a basis before studying the advanced topics of the OOP paradigm.